Impacts of conversion of cropland to grassland on the C-N-P stoichiometric dynamics of soil, microorganisms, and enzymes across China: A synthesis - Li, Ying; Sang, Jianhui; Zou, Canwei; Zhang, Qingping; Yang, Qian; Xu, Gang; Kim, Dong-Gill; Denton, Matthew D.; Rosa Carmona, Carmen; Zhao, Hongyang; Mao, Yanting; Mao, Liping; et al. (Elsevier, 2024)
In response to escalating land degradation, the conversion of cropland to grassland has emerged as a crucial mitigation strategy. This conversion has a significant influence on the stoichiometry of soil, microorganisms, and enzymes, specifically in relation to carbon (C), nitrogen (N), and phosphorus (P). A meta-analysis was conducted with 371 observations from 122 articles investigating the impacts of cropland to grassland conversion on the C-N-P stoichiometric dynamics of soils, microorganisms, and enzymes across China. The findings revealed that conversion significantly increased soil C:P (9.0%), soil N:P (5.6%), microbial C:N (15.5%), and notably, microbial C:P by 57.9%. This substantial increase in microbial C:P indicates that microbial communities are highly responsive to land use conversion. Contrastingly, the enzyme C:P ratio decreased by 19.8%, suggesting microbial adaptation to changing nutrient availability. The duration of conversion was positively correlated with soil C:P and N:P ratios, implying that relative P availability may decrease as conversion progresses. However, duration was negatively correlated with microbial C:P. Environmental factors such as clay content, mean annual temperature, and mean annual precipitation were positively correlated with microbial C:N and negatively correlated with microbial N:P, while soil pH was inversely correlated with microbial C:N. These results suggest the substantial influence of cropland to grassland conversion on soil, microbial, and enzyme stoichiometry, with particularly pronounced effects on microbial communities. The observed shifts in stoichiometric ratios suggest changes in nutrient cycling and availability following conversion. While these changes are primarily attributed to the land use conversion, we acknowledge that alterations in management practices, such as reduced fertilization, likely contribute to the observed stoichiometric shifts. Our findings emphasize the importance of considering both environmental factors and management practices when implementing grassland conversion initiatives.
Keywords: cropland to grassland conversion; soil stoichiometry; microbial C-N-P stoichiometry; enzyme C-N-P stoichiometry